2021
DOI: 10.3390/plants10010075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Bacterial Wilt Resistant Eggplant Rootstocks for Grafting Tomato

Abstract: Bacterial wilt (BW) is one of the most economically important diseases of tomato and eggplant in the tropics and subtropics, and grafting onto resistant rootstocks can provide an alternative and effective solution to manage soil-borne bacterial in these crops. This study was conducted to evaluate the BW resistance and agronomic potential of newly identified eggplant accessions as rootstocks for tomato grafting. Five BW resistant eggplant accessions (VI041809A, VI041943, VI041945, VI041979A, and VI041984) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“… Rivard et al (2012) grafted tomatoes with resistant rootstocks to control bacterial wilt (BW) caused by R. solanacearum , and the results showed that the incidence of BW in grafted plants decreased by 30–50% compared with that of the non-grafted plants. Manickam et al (2021) used five BW-resistant eggplant germplasms as rootstocks for grafting tomato, after inoculation with BW, the disease incidence for the grafted plants was 0 to 20%, and the tomato yield of grafted eggplant rootstocks was higher than that of non-grafted tomatoes. Lin et al (2005) introduced the Arabidopsis NPR1 gene into a tomato cultivar with resistance to tomato mosaic virus (ToMV), and the results of disease screens against eight important tropical diseases revealed that the transgenic lines exhibited significantly enhanced resistance to bacterial wilt (BW) and fusarium wilt (FW).…”
Section: Discussionmentioning
confidence: 99%
“… Rivard et al (2012) grafted tomatoes with resistant rootstocks to control bacterial wilt (BW) caused by R. solanacearum , and the results showed that the incidence of BW in grafted plants decreased by 30–50% compared with that of the non-grafted plants. Manickam et al (2021) used five BW-resistant eggplant germplasms as rootstocks for grafting tomato, after inoculation with BW, the disease incidence for the grafted plants was 0 to 20%, and the tomato yield of grafted eggplant rootstocks was higher than that of non-grafted tomatoes. Lin et al (2005) introduced the Arabidopsis NPR1 gene into a tomato cultivar with resistance to tomato mosaic virus (ToMV), and the results of disease screens against eight important tropical diseases revealed that the transgenic lines exhibited significantly enhanced resistance to bacterial wilt (BW) and fusarium wilt (FW).…”
Section: Discussionmentioning
confidence: 99%
“…'Yatsubusa' grafted onto the rootstock of another variety ('Spanish Paprika') led to a significantly higher number of nodes and branches on the main stem [44]. Overall, the field survival and growth performance of successful graft combinations under disease-infested conditions are the direct effect of rootstock-provided reduced disease incidence [45].…”
Section: Vegetative Growth Parametersmentioning
confidence: 93%
“…Grafting is an agronomic technique intensively used in the horticultural industry to boost plant resistance toward biotic and abiotic stresses [ 5 ]. Grafting is extensively utilized in tomato to boost yield or quality, while also increasing resistance to a variety of stressors, including cold stress and root-knot disease [ 6 , 7 ]. The improvement of cold tolerance by grafting onto cold-tolerant rootstock can be attributed to several physiological mechanisms: (i) avoidance of damage by closing stomata more quickly than sensitive genotypes when temperature decreases [ 8 ]; (ii) improvement of scion tolerance by increasing osmoprotectants (free proline, betaine, and soluble sugar) in the cytosol [ 9 ]; (iii) elimination of oxygen radicals by increasing the contents of detoxifying substances (glutathione) or antioxidant enzymes (peroxidase and ascorbate peroxidase) [ 10 ]; (iv) modulation of cold tolerance by affecting photosynthesis, and carbon and nitrogen metabolism [ 11 ]; and (v) maintenance of stomatal conductance and nitrogen content, thus achieving better plant establishment and growth performance at suboptimal temperatures [ 12 ].…”
Section: Introductionmentioning
confidence: 99%